A pattern language to join early and late requirements - Martínez, Alicia (2005)
At present, the early phase of Requirements Engineering is a new research area in the Software Engineering field. This phase is concerned with the analysis of the organizational context in which a software system will be used. The models used in this phase allow us to describe an organizational environment using actors, goals, business processes and relationships. The late phase of Requirements Engineering, which is focused on representing the expected functionality of the software system, is more developed, so there are multiple techniques and tools to describe the software system that will be developed inside its operational environment. However, although there are methodologies which give separate support to each phase of requirements engineering, the development of methods to derive late requirements from the early requirements in a methodological way has been neglected in recent research works. This is due, in great measure, to the large difference between the abstraction levels of these two specification models. The objective of this paper is to propose a pattern language which allows us to reduce the abstraction level between early requirements and late requirements in a systematic way. This is done in an MDA-based approach.